CONVERSATION ANALYSIS (Case Study of Conductor-Passenger Conversation in Public Transportation) - Akhmad Baihaqi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2017)
This paper is intended to understand how conversational pattern is occurred between conductor and passenger in public transportation. The research was conducted through case study. Data of the research were taken from the conversation transcriptions between conductor and passenger in public transportation. The result of the research shows that the most turn taking patterns in conversation are interruption, and the types of speech acts that mostly occurred are illocutionary act of directive, assertive, and expressive utterances. The research also finds the existing pattern of adjacency pairs, sequences, and implicature.